Meno II: A self-referential Socratic dialogue about memory and computer programming (The Reasoner, 2025)
We provide a Socratic dialogue in which Meno challenges Socrates' principle that all learning is actually the remembering of things known but forgotten. Meno claims if Socrates' principle holds, then Meno should already know the contents of the ongoing dialogue. Meno challenges Socrates to help Meno recall those contents, claiming Socrates cannot do this, lest Meno could immediately say the opposite of whatever he supposedly recalls he was about to say. Socrates eventually succeeds at Meno's challenge in an unexpected manner.
Keywords: anamnesis; Meno; self-reference